Modeling the Oil Price Influences Upon the Energy Sector in the Macroeconomic Context. Empirical Evidence from Central and Eastern European Countries - Dumiter , Florin Cornel; Nicoară , Ștefania Amalia; Nicoară , Samuel; Bențe , Cristian; Păiușan, Luminița (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2025)
The oil price influences and tendencies have gained, lately major developments both at the European level and on the international level. Moreover, several interconnections between the energy sector and oil price influences have become the panacea of several important research and studies. In this article, we provide a qualitative and quantitative approach to the interconnections manifested between oil price movements and the developments of the energy sector. The study is focused on Central and Eastern European Countries which have similarities and differences both at the energy sector level and economy level. The econometric techniques used in this study reveal the importance of the causality relationship between oil price movements and the energy sector taking into account the macroeconomic context. The conclusions of this study highlight some important fine-tuning aspects that must be recalibrated in Central and Eastern European Countries to increase the economic outcomes, strengthen the energy sector, and respond properly to the oil price movement trends.